PTU-028 Genome-wide association study of MRI liver iron content in UK biobank identifies 3 susceptibility variants. Issue 2 (June 2019) - Parisinos, Constantinos; Wilman, Henry; Kelly, Matt; Neubauer, Stefan; Thomas, Louise; Bell, Jimmy; Hingorani, Aroon; Patel, Riyaz; Hemingway, Harry; Banerjee, Rajarshi; Yaghootkar, Hanieh
Abstract : Background and aims: Excess liver iron content is common, affecting approximately 10% of the population, and observationally associates with hepatic and extrahepatic diseases such as liver fibrosis, hepatocellular carcinoma and metabolic syndrome 1 . Genome wide association studies (GWAS) on MRI determined liver iron content, compared to circulating iron traits, permit detection of liver-specific susceptibility loci. Here we aim to find genetic variants influencing liver iron content, using data from UK Biobank. Methods: Data was acquired from UK Biobank (application 9914). Liver phenotypes were calculated from MRI data by trained analysts using LiverMultiScanTM. We used GEMMA to perform a GWAS of MRI scan measures of liver iron in 8, 289 individuals of European ancestry. We adjusted for age, sex, BMI, genotyping array, and population structure. Results: We identified three independent genetic variants (rs1800562 & rs1799945 in HFE, rs855791 in TMPRSS6 ) associated with liver iron content at genome-wide significance (p < 5x10 −8 ). These variants have been reported previously to be associated with blood markers of iron levels. Mendelian randomisation analysis provided evidence that higher central adiposity plays a causal role in increased liver iron content. Phenome-wide association analysis demonstrated that liver iron increasing alleles in HFE were also associated with high blood pressure, liver cirrhosis, hepatic and extrahepatic malignancies, neuro-psychiatric, endocrine and rheumatological conditions, but inversely associated with LDL cholesterol, heart disease and gallbladder diseases. The liver iron increasing allele in TMPRSS6 was inversely associated with lipidaemias and ischaemic heart disease. Conclusion: Our study provides genetic evidence that mechanisms underlying liver iron content are mostly systemic and not organ specific. The identification of loci which affect circulating iron traits provide genetic validation of the utility of MRI for a fast and non-invasive assessment of liver iron content. Reference: Deugnier, Y., Bardou-Jacquet, É. & Lainé, F. Dysmetabolic iron overload syndrome (DIOS). Presse Med. 46, e306–e311 (2017).